Implementasi Kepemimpinan Tranformasional HRD Melalui Kepemimpinan Tidak Langsung di Widuri Indonesia Restaurant - Bilqis Putri Agustina; Repa Rahmawati; Muhammad Rizki Fadhilah; Dewo Pangestu; Hani Humaeriyah (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to analyze the role of Human Resource Development (HRD) in implementing transformational leadership through an indirect leadership mechanism in human resource management at Widuri Indonesian Restaurant. The study employed a qualitative approach with a descriptive method. Data were collected through in-depth, semi-structured interviews with the HRD as the main informant. The data were analyzed using qualitative techniques, including data reduction, data display, and conclusion drawing. The findings indicate that HRD does not exercise leadership through direct operational involvement, but rather functions as a strategic and functional leader by formulating human resource policies, developing standard operating procedures and job descriptions, planning and controlling manpower, and mentoring outlet leaders. The leadership practices observed reflect the four dimensions of transformational leadership—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—which are implemented systematically through organizational systems, formal communication mechanisms, and structured delegation. This study concludes that transformational leadership at Widuri Indonesian Restaurant is exercised in an indirect form, where leadership values, vision, and direction are transmitted through organizational structures and work systems rather than through daily direct interactions. These findings contribute to the literature on transformational leadership, particularly in the context of HRD functions within the restaurant industry.